2007
DOI: 10.1016/j.virusres.2007.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Reduced infection in mosquitoes exposed to blood meals containing previously frozen flaviviruses

Abstract: The increased difficulty and expense of using live animals for delivering infectious blood meals in arthropod-borne virus vector competence experiments has resulted in an increase in the use of artificial feeding systems. Compared to live hosts, artificial systems require higher viral titers to attain mosquito infection, thereby limiting the utility of such systems with low or moderate titer virus stocks. Based on the report that freshly propagated virus is more infectious than previously frozen virus, we dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 14 publications
0
30
2
Order By: Relevance
“…collecting supernatant directly from cells at the peak infection for use in artificial blood-meals without previous freezing) [2527]. Since little is known about mosquito infections with ZIKV, we first tested whether frozen-thawed virus was equivalent to fresh virus in mosquito infections.…”
Section: Resultsmentioning
confidence: 99%
“…collecting supernatant directly from cells at the peak infection for use in artificial blood-meals without previous freezing) [2527]. Since little is known about mosquito infections with ZIKV, we first tested whether frozen-thawed virus was equivalent to fresh virus in mosquito infections.…”
Section: Resultsmentioning
confidence: 99%
“…Also, in the case of DENV and St. Louis encephalitis virus, frozen stocks are less infectious for Ae. aegypti mosquitoes than freshly harvested, cell culture–derived virus ( 30 ). The FSS 13025 strain of Zika virus infected only 75% of Salvador Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that fresh preparation of low-titered SLEV is an effective method for infecting mosquitoes by artificial feeding systems 31. Consequently, a T-75 cm 2 flask of confluent African green monkey (Vero) cells was inoculated with 0.15 mL of SLEV stock previously determined by plaque assay to have 6.0 logs plaque-forming units (PFU)/mL.…”
Section: Methodsmentioning
confidence: 99%